MiR-27b-3p promotes migration and invasion in colorectal cancer cells by targeting HOXA10. Issue 12 (6th December 2019) - Yang, Xiangling; Chen, Junxiong; Liao, Yao; Huang, Lanlan; Wen, Chuangyu; Lin, Mengmeng; Li, Weiqian; Zhu, Yonglin; Wu, Xiaojian; Iwamoto, Aikichi; Wang, Zhongyang; Liu, Huanliang
Abstract: Purpose: Dysregulation of microRNAs (miRNAs) contributes to tumor progression via the regulation of the expression of specific oncogenes and tumor suppressor genes. One such example, miR-27b-3p, has reportedly been involved in tumor progression in many types of cancer. The aim of the present study was to delve into the role and the underlying mechanism of miR-27b-3p in colorectal cancer (CRC) cells. Methods: In the present study, we detected the expression level of miR-27b-3p by RT-PCR. The effect of miR-27b-3p overexpression on cell proliferation in CRC cells was evaluated by cell counting and Edu assays. Transwell migration and invasion assays were used to examine the effects of cell migration and invasion. Bioinformatics, luciferase reporter assay and western blot assay were performed to identify the target of miR-27b-3p. Results: Here, we have demonstrated that although miR-27b-3p can affect cell morphology, it has no observable effect on the proliferation of CRC cells. However, it significantly promotes the migration and invasion of CRC cells. We discovered that HOXA10 was a newly identified target of miR-27b-3p in CRC cells, as confirmed by bioinformatics, western blots and dual luciferase reporter assay. Furthermore, the overexpression of miR-27b-3p or the suppression of HOXA10 can activate the integrin β1 signaling pathway. In conclusion, our results reveal a new function of miR-27b-3p that demonstrates its ability to promote CRC cell migration and invasion by targeting the HOXA10/integrin β1 cell signal axis. Conclusion: This may provide a mechanism to explain why miR-27b-3p promotes CRC cell migration and invasion.